2019
DOI: 10.1002/lary.28312
|View full text |Cite
|
Sign up to set email alerts
|

Gastrostomy Utilization by Oropharyngeal Cancer Patients Is Partially Driven by Swallowing Function

Abstract: ObjectiveOropharyngeal squamous cell carcinoma (OPSCC) incidence is rapidly increasing, as are survival rates, in large part due to the human papillomavirus (HPV). Treatment intensity, however, has remained unchanged, making treatment‐related toxicity (i.e., dysphagia) a critical problem for an increasing number of patients. The primary objective of this study was to determine whether pretreatment objective swallowing measures can predict percutaneous fluoroscopic guided gastrostomy tube (PFG) utilization duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…However, objectively measured swallow function was not associated with PEG utilization. Development of PEG placement algorithms (reactive vs. prophylactic) therefore require additional inputs/metrics 40 . Long‐term gastrostomy tube dependence following TORS is rare, particularly in patients that receive surgery alone 41 .…”
Section: Discussionmentioning
confidence: 99%
“…However, objectively measured swallow function was not associated with PEG utilization. Development of PEG placement algorithms (reactive vs. prophylactic) therefore require additional inputs/metrics 40 . Long‐term gastrostomy tube dependence following TORS is rare, particularly in patients that receive surgery alone 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Although HNC accounts for only 4% of all cancer it suffers the highest treatment‐related morbidity 3,22,23 . Consequently, the experience of having been diagnosed with HNC produces reactions that can impact critical activities such as swallowing, feeding and overall quality of life 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Although HNC accounts for only 4% of all cancer it suffers the highest treatment‐related morbidity 3,22,23 . Consequently, the experience of having been diagnosed with HNC produces reactions that can impact critical activities such as swallowing, feeding and overall quality of life 3 . One method of ameliorating the effects of ablative HNC treatment is early swallow exercise aimed at promoting movement of the swallowing musculature and maintaining oral intake 4 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DIGEST is a simple but robust tool with evidence of uptake in clinical and research practice. [6][7][8][9][10][11] Since its implementation began in 2016, clinical and research speechlanguage pathology users of DIGEST have identified areas for refinement specifically related to the grading of mild safety impairments. The objective of this work was, therefore, to assess the performance of refined DIGEST safety grading criteria in DIGEST version 2 (DIGEST v2 ) and the structural validity of DIGEST v2 .…”
Section: Introductionmentioning
confidence: 99%